Math, asked by zulfathimah, 1 year ago

3a-2a-ab-(a-b+ab)+3ab+b+a

Answers

Answered by Anonymous
2
=3a-2a-ab-a+b-ab+3ab+b+a

=a+ab+2b
Answered by sonalithakur82
2

Answer:

hope it helps

Step-by-step explanation:

3a-2a-ab-(a-b+ab)+3ab+b+a

=3a-2a-ab-a+b-ab+3ab+b+a

=3a-a+a-2a-ab-ab+3ab+b+b

=3a-2a-2ab+3ab+2b

=a+ab+2b


sonalithakur82: dont change
LostMagician: ohk
LostMagician: I kept it coz.... it's my gaming name
sonalithakur82: ooo wow thats superb
LostMagician: accha aap mujhe jyada hawe mei mat udao
LostMagician: ??
sonalithakur82: waisa kuchh hai nhi i just thought it was cool so i said it
sonalithakur82: thik hai na
LostMagician: ohk
LostMagician: mujhe nhi lagta itna cool hai... so I said
Similar questions